The effect of Shari’ah implementation towards soci-economic development of Muslim society in Katagum local government of Bauchi State, Nigeria / Jamila Ahmad Aminu - Ahmad Aminu, Jamila (2020)
The study investigated and examined the effect of Shari’a implementation in Katagum Local Government Area on Socioeconomic Development of its people. The research aim finding the effect of Shari’a implementation of marriage activities, trade and commerce and some ill-vices like prostitutions, gambling and alcoholism among others. Four research questions were asked. The survey designed and a systematic sampling techniques were used to select a sample of 100 peoples both men and women from five towns contained in the local government. Questionnaire was used and method of data collected and distributed to the respondents the data was analyses using simple percentage. Only 92 respondents who duly completed, the findings shows that Shari’a implementation has positive effects on marriage activities where most of the marriage innovations were discarded, the mode of commercial transactions were sanitized and ill-vices shunt away. Moreover some might clubs that are in existence before Shari’a were transformed in to Islamic centers.